Sertifikat ELSIMIL (Elektronik Siap Nikah dan Hamil) sebagai Syarat Pendaftaran Nikah Perspektif Saddu Żarī'ah: ELSIMIL Certificate as a Requirement for Marriage Registration from Saddu Żarī’ah Perspective - Firosyan Noor Firdausi; Muhammad Wahid Abdullah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
In order to prevent stunting from upstream to downstream, BKKBN has developed a strategy in the form of the Electronic Ready for Marriage and Pregnancy (ELSMIL) application as a health screening tool for prospective brides and grooms, which was inaugurated in June 2023. Prospective brides and grooms are encouraged to register for the Elsimil application 3 months in advance to take a series of tests and screenings. If the prospective bride and groom pass, they will receive an ELSIMIL certificate which then becomes an administrative requirement at KUA. This research aims to analyze in more depth whether this policy is in accordance with or contrary to the concept of saddu żarī'ah, considering that this is not a legal requirement for marriage in Islam. This research uses normative juridical methods by reviewing library materials and secondary data, and uses normative qualitative as an analysis technique. The results of this research show that the BKKBN strategy to reduce stunting through the Elsimil application is an implementation of the saddu żarī'ah concept. This is because the main purpose of the Elsimil application is as a preventive step in preventing risky pregnancies and a catin health monitoring tool to achieve ideal pregnancy conditions, which is in line with the saddu żarī'ah concept.